Coordination, Comprehensiveness and Continuity as the Quality Measures of Remote Primary Healthcare in Poland - Liliana Hawrysz; Renata Walczak; Agnieszka Bitkowska; Piotr Korneta; Wioletta Pomaranik; Magdalena Kludacz-Alessandri (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: The purpose of this article is to examine the quality of remote primary healthcare in Poland measured through three dimensions: coordination, comprehensiveness, and continuity (3Cs) and examine the relationship between them.